k = 0 ∑ ∞ ( 4 k + 2 3 ln ( 4 k + 2 ) − 4 k + 3 ln ( 4 k + 3 ) − 4 k + 4 ln ( 4 k + 4 ) − 4 k + 5 ln ( 4 k + 5 ) ) = 2 3 ln 2 − 3 ln 3 − 4 ln 4 − 5 ln 5 + 6 3 ln 6 − 7 ln 7 − 8 ln 8 − 9 ln 9 + 1 0 3 ln 1 0 − ⋯
Evaluate the sum above. Give your answer to 2 decimal places.
Notation: ln ( ⋅ ) denotes the natural logarithm.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution, but I think there’s a typo after ∑ k = n + 1 2 n + 1 ( 2 k + 2 ln ( 2 k + 2 ) − 2 k + 3 ln ( 2 k + 3 ) ) → 0 .
This sum approaches zero as n → ∞ .
Problem Loading...
Note Loading...
Set Loading...
Thought it was insanely difficult during the contest because the sum doesn't converge absolutely and now I think I got it. Rip. :(
To avoid dealing with problems in absolute convergence, we deal with the n -th partial sum. That is, k = 0 ∑ n ( 3 ⋅ 4 k + 2 ln ( 4 k + 2 ) − 4 k + 3 ln ( 4 k + 3 ) − 4 k + 4 ln ( 4 k + 4 ) − 4 k + 5 ln ( 4 k + 5 ) ) = 3 ⋅ 2 ln 2 − 3 ln 3 − 4 ln 4 − 5 ln 5 + ⋯ + 3 ⋅ 4 n + 2 ln ( 4 n + 2 ) − 4 n + 3 ln ( 4 n + 3 ) − 4 n + 4 ln ( 4 n + 4 ) − 4 n + 5 ln ( 4 n + 5 ) . Because the sum is finite here, we have no issue of convergence and therefore can do the following conversion: k = 0 ∑ n ( 3 ⋅ 4 k + 2 ln ( 4 k + 2 ) − 4 k + 3 ln ( 4 k + 3 ) − 4 k + 4 ln ( 4 k + 4 ) − 4 k + 5 ln ( 4 k + 5 ) ) = k = 0 ∑ n ( 4 k + 2 ln ( 4 k + 2 ) − 4 k + 3 ln ( 4 k + 3 ) + 4 k + 4 ln ( 4 k + 4 ) − 4 k + 5 ln ( 4 k + 5 ) ) + k = 0 ∑ n 2 ( 4 k + 2 ln ( 4 k + 2 ) − 4 k + 4 ln ( 4 k + 4 ) ) Also notice that k = 0 ∑ n 2 ( 4 k + 2 ln ( 4 k + 2 ) − 4 k + 4 ln ( 4 k + 4 ) ) = k = 0 ∑ n ( 2 k + 1 ln 2 + ln ( 2 k + 1 ) − 2 k + 2 ln 2 + ln ( 2 k + 2 ) ) So we have k = 0 ∑ n ( 4 k + 2 ln ( 4 k + 2 ) − 4 k + 3 ln ( 4 k + 3 ) + 4 k + 4 ln ( 4 k + 4 ) − 4 k + 5 ln ( 4 k + 5 ) ) + k = 0 ∑ n 2 ( 4 k + 2 ln ( 4 k + 2 ) − 4 k + 4 ln ( 4 k + 4 ) ) = k = 0 ∑ 2 n + 1 ( 2 k + 2 ln ( 2 k + 2 ) − 2 k + 3 ln ( 2 k + 3 ) ) + k = 0 ∑ n ( 2 k + 1 ln 2 + ln ( 2 k + 1 ) − 2 k + 2 ln 2 + ln ( 2 k + 2 ) ) = ln 2 k = 0 ∑ n ( 2 k + 1 1 − 2 k + 2 1 ) − 2 n + 2 ln ( 2 n + 2 ) + k = n + 1 ∑ 2 n + 1 ( 2 k + 2 ln ( 2 k + 2 ) − 2 k + 3 ln ( 2 k + 3 ) ) Now, notice that x ln x is a decreasing sequence with limit 0 as x → ∞ . Thus ∑ k = 0 2 n + 1 ( 2 k + 2 ln ( 2 k + 2 ) − 2 k + 3 ln ( 2 k + 3 ) ) is an alternating sum hence converges), which means that ∑ k = n + 1 2 n + 1 ( 2 k + 2 ln ( 2 k + 2 ) − 2 k + 3 ln ( 2 k + 3 ) ) → 0 as n → 0 . It is also well known that ∑ k = 0 n ( 2 k + 1 1 − 2 k + 2 1 ) → ln 2 as n → ∞ . Therefore lim n → ∞ ln 2 ∑ k = 0 n ( 2 k + 1 1 − 2 k + 2 1 ) − 2 n + 2 ln ( 2 n + 2 ) + ∑ k = n + 1 2 n + 1 ( 2 k + 2 ln ( 2 k + 2 ) − 2 k + 3 ln ( 2 k + 3 ) ) = ( ln 2 ) 2 + 0 + 0 = ( ln 2 ) 2 Giving ( 0 . 6 9 3 ) 2 = taking 0 . 4 8